Hydrotunnel installation for spraying potato plantations with a jet pump - Arendarenko, V.; Ivanov, O.; Shpylka, M.; Simonov, K. (Scientific Progress & Innovations, 2024)
In agriculture, rod sprayers are used to control the Colorado potato beetle in potato fields. Most serial sprayers do not provide treatment with the working liquid of the lower leaves of the potato bushes, and part of this substance flows out of the bush and falls on the ground. Such treatment increases the pesticide load on the soil and the environment. To eliminate this shortcoming, a tunnel-type hydraulic installation is proposed. Spraying of potatoes in such an installation takes place in the tunnel with the help of centrifugal sprayers, and jet pumps are used to pump out the liquid flowing from the trays. This installation ensures accurate dosing of the chemical preparation, uniform distribution of the preparation over the entire surface of the bush. Wastewater is also collected and used for re-spraying, which reduces the pesticide load on the soil. Based on the equation of the fluid balance in the hydraulic nodes of the hydraulic system of the hydrotunnel installation and the pressure balance for the isolated hydraulic branch of the installation, theoretical studies were performed with the method of calculating the necessary hydrodynamic pressure on the sprinklers and determining the parameters of the pipe equipment elements. On the basis of theoretical transformations, it was established that the speed of pumping the working fluid from the trays depends on the product of the ratio of the diameter of the supply tube to the diameter of the nozzle of the jet pump and the initial speed of the working fluid. At the same time, this dependence has a hyperbolic dependence and has an increasing character in the entire range of variation of diametrical dimensions. It was also established by calculation that the initial speed of movement of the working fluid has a determining effect on the formation of the intensity of the fluid supply from the nozzles. Thus, increasing the initial speed from 1 m/s to 2 m/s with a ratio of diameters at the level of six makes it possible to increase the feed speed from 36 to 72 m/s. It was additionally theoretically proven that the increase in the vacuum level in the chamber of the jet pump is directly proportional to the ratio of diameters at the inlet and outlet of the nozzle.